2022
DOI: 10.1038/s41598-022-10118-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the association between uric acid levels and chronic kidney disease

Abstract: The function of uric acid (UA) in the genesis and evolution of chronic kidney disease (CKD) has motivated numerous studies, but the results remain inconclusive. We sought to conduct a systematic review and meta-analysis of cohort studies aiming to analyze the association of UA levels with the incidence and progression of CKD. Pubmed/Medline, Lilacs/Bireme and Web of Science were searched to identify eligible studies, following the PRISMA protocol. Data were presented for CKD incidence and progression separatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 57 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…This regulation of urinary acid-base balance not only helps lower serum uric acid levels but may also alleviate the burden on the kidneys. [ 23 , 24 ] Long-term high UA levels can lead to kidney stones and renal damage; therefore, by lowering serum uric acid levels, alkaline water may offer indirect benefits in protecting kidney health. Additionally, by promoting UA excretion, alkaline water may indirectly reduce UA deposition in joints and soft tissues, thereby alleviating or preventing symptoms of gouty arthritis.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…This regulation of urinary acid-base balance not only helps lower serum uric acid levels but may also alleviate the burden on the kidneys. [ 23 , 24 ] Long-term high UA levels can lead to kidney stones and renal damage; therefore, by lowering serum uric acid levels, alkaline water may offer indirect benefits in protecting kidney health. Additionally, by promoting UA excretion, alkaline water may indirectly reduce UA deposition in joints and soft tissues, thereby alleviating or preventing symptoms of gouty arthritis.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…However, another study showed different results about an inverse relationship between SUA levels and protection from CKD incidence and progression. Lower UA levels were protective for the risk of CKD incidence (RR 0.65 [95% CI 0.56-0.75]) and progression (RR 0.55 [95% CI 0.44-0.68]) ( 28 ). The results that we obtained also support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…These include CVD, HTN, CKD, and most features of the metabolic syndrome (obesity, insulin resistance, etc.) 13 14 The association of hyperuricemia with these disorders has been documented in both children and adults.…”
Section: The Role Of Uric Acid In the Pathogenesis Of Diseasementioning
confidence: 99%